PENGARUH KOMPETENSI PROFESIONAL GURU DAN LITERASI INFORMASI TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN KORESPONDENSI JURUSAN ADMINISTRASI PERKANTORAN DI SMK NEGERI 1 MEDAN T.P 2018/2019 - Cici Hardiyanti Utami; Sri Muthmainnah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2019)
The problem in this study is the low student achievement. The low learning achievement is due to the lack of professional competence of teachers and information literacy so that it has an impact on student learning achievement in the subject matter of correspondence in the department of administration at SMK Negeri 1 Medan T.P 2018/2019. The purpose of this study was to determine the effect of teacher professional competence and information literacy on student learning achievement in correspondence subjects in the administration department at SMK Negeri 1 Medan T.P 2018/2019. This research was conducted at SMK Negeri 1 Medan. The population in this study were class X AP students totaling 143 people and a sample of 59 people. The instrument used to measure teacher professional competence and information literacy in the form of questionnaires totaling 20 questions for each variable and document study (DKN) for variable student achievement. The validity of the test was tested using the product moment correlation technique. Tests are tested using the Alpha Cronbarch formula. Then the data is analyzed by multiple linear regression formulas. Next to test the hypothesis partially t test and simultaneously use the test f. From the results of data analysis with partial testing of Professional Teacher Competence (X1) the value of tcount > ttable (8.985> 1.673) and the partial test of Information Literacy (X2) the value of tcount> ttable (2.947> 1.673), means that if the teacher teaches well then increases student achievement. Simultaneous testing obtained Fcount of 134,370. Then from these results the value of Fcount> Ftable (134,370> 3,16). Based on the results of the research conducted, it can be seen that the professional competence of teachers and information literacy has a positive and significant influence on student learning achievement in the subject matter of office administration department correspondence at SMK Negeri 1 Medan T.P 2018/2019.